The Status of the Secondary Wife: its Development in Ancient Near Eastern Law. A Study and Comprehensive Index - McComiskey, Thomas Edward (1965)
Ph.D.; University Microfilms Order No. 65-14,430. Microfilm $3.00; Xerography $9.45; Dissertation Abstracts 27/5 (Ann Arbor, Mich., November 1966) 1308-A.